The role of physicians in rationing cancer care: attitudes of German oncologists - Fernau, Sandra; Mehlis, Katja; Winkler, Eva C. (Oncology research and treatment, 2017)
Background: Against the background of limited resources, the rise in the cost of therapy as well as in the number of cancer patients fuels the discussion about the necessity to ration, i.e., setting limits to beneficial treatment for cost reasons. Recently, we presented the self-reported prevalence of bedside rationing among German oncologists. Here, we describe oncologists' views on cost containment strategies and their role therein. Methods: We performed an online survey including structured questions and free field sections with the members of the German Society of Hematology and Oncology. Results: In the perception of oncologists, cost considerations and negotiations are gaining in importance and consume considerable working time. This negatively affects job satisfaction in 72% of the 345 respondents. Oncologists are concerned that the quality of care will suffer from rationalization and implicit rationing. They are ambivalent as to who is best suited to decide about resource rationing: 66% support the view that limits for costly procedures should be set by a form of commission; nevertheless, 48% consider physicians as the best decision makers in these situations. Conclusion: We suggest a broad public discussion and an interdisciplinary debate among the oncology community to define and legitimize decisions on rationing by setting explicit criteria.